PENGARUH KEPEMIMPINAN, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT.K3/SIL Ketahun Begkulu Utara) - Renita Apriyanti; Khairul Bahrun; Meilaty Finthariasari ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
The purpose of this study is to find out how the influence of leadership, reward and punishment on employee performance at PT. K3 / SIL Ketahun Bengkulu Utara . This type of research used in this study is a quantitative approach method. The sample in this study amounted to 110 respondents with a sampling technique using total sampling, while the sample was taken with a total sampling technique. Data analysis techniques using descriptive and inferential analysis in this study. Based on the results of the study can be seen leadership has no significant effect on employee performance at PT. K3 / SIL Ketahun Bengkulu Utara because a significant value of 0.648 is not significant to the performance of employees at PT. K3 / SIL Ketahun Bengkulu Utara because the significant value is greater than 0.05, based on the results of the study can be seen Reward significantly influence employee performance at PT. K3 / SIL Ketahun Bengkulu Utara because a significant value of 0.003 is significant on the performance of employees at PT. K3 / SIL Ketahun Bengkulu Utara because the significant value is smaller than 0.05 and based on the results of the study can be seen Punishment significantly influence employee performance at PT. K3 / SIL Ketahun Bengkulu Utara because a significant value of 0,000 is significant to the performance of employees at PT. K3 / SIL Ketahun Bengkulu Utara because the significant value is smaller than 0.05. The results in this study indicate that all dimensions of leadership, reward and punishment affect the performance of employees at PT. K3 / SIL Ketahun Bengkulu Utara. Keywords: Leadership, Reward, Punishment and Employee Performance